Strategic Tillage in Dryland No-Tillage Crop Production Systems - A. K. Obour; J. D. Holman; A. J. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2019)
Emerging challenges in continuous no-till (NT) systems require developing flexible management strategies that will minimize the impacts of herbicide resistant (HR) weeds and nutrient stratification on soil and crop productivity. This study evaluated the effectiveness of strategic tillage (ST) operations as an option to redistribute soil nutrients and acidity, control perennial grass and HR weeds, and improve crop yields following tillage of an otherwise long-term NT soil. Treatments were five crop rotations: 1) continuous winter wheat (WW); 2) wheat-fallow (WF); 3) wheat-sorghum-fallow (WSF); 4) continuous sorghum (SS); and 5) sorghum-fallow (SF) as main plots. Sub-plots were reduced tilled (RT), continuous NT, and ST of long-term NT. Grass and herbicide resistant weeds were reduced with tillage. Irrespective of crop rotation, soil water content at wheat planting was significantly less with RT treatments compared to NT or ST. Soil water content with NT was not different from that of ST under cropping systems with fallow (WF or WSF). Tillage (ST or RT) reduced soil water content at wheat planting in WW system. Winter wheat grain yields decreased with increasing cropping intensity, WF (26-48 bu/a)>WSF (22-33 bu/a)>WW (15-19 bu/a). Averaged across years and crop rotations, wheat yield with ST was 30 bu/a, which was greater than the NT (23 bu/a) or RT (28 bu/a) systems, mostly due to better weed control and increased nutrient availability. Sorghum grain yield over the 2 years with ST (63 bu/a) was not different from that of NT (61 bu/a), but were both greater than that of RT (54 bu/a). Increasing cropping intensity reduced sorghum grain yield, average grain yield with SF was 73 bu/a, similar to WSF (68 bu/a), but greater than SS (38 bu/a). Tillage had no effect on soil bulk density. However, increasing cropping intensity lowered the bulk density measured in the upper 0 to 2 in. of the soil. Tillage and crop rotation effects on soil organic matter (SOM), pH, and nutrient concentrations occurred only in the top 0- to 2-in. depth. The SOM, iron (Fe), and manganese (MN) concentrations were greater in soils under WW compared to WF or WSF. Soil pH and potassium (K) were least in soils under WW. The SOM concentration in the top 0 to 2 in. with NT was 3.34%, which was similar to that of soil under ST (3.02%) but both were greater than RT (2.65%). Nitrate-N concentration increased with ST but ammonium-N concentration was greatest in soils under NT. Our results suggest ST could provide a mitigation option for HR weeds in NT crop production with little impact on crop yields and soil chemical properties.
Keywords: dryland; herbicide-resistant weeds; no-tillage; strategic tillage